Investigation of the Material Basis Underlying the Correlation between Presbycusis and Kidney Deficiency in Traditional Chinese Medicine via GC/MS Metabolomics. (25th November 2013) - Dong, Yang; Ding, Yue; Liu, Pu-Zhao; Song, Hai-Yan; Zhao, Yu-Ping; Li, Ming; Shi, Jian-Rong
Abstract : Objective . To investigate the correlation between presbycusis and kidney deficiency as defined by traditional Chinese medicine (TCM) and its material basis from the perspective of metabolism. Methods . Pure-tone audiometry was used to test auditory function. A kidney deficiency symptom scoring table was used to measure the kidney deficiency accumulated scores of the research subjects. Gas chromatography/mass spectrometry (GC/MS) was used to measure the metabolites in the urine samples from 11 presbycusis patients and 9 elderly people with normal hearing. Results . Hearing loss in the elderly was positively correlated with kidney deficiency score in TCM. There were significant differences in urine metabolite profile between the presbycusis patients and the controls. A total of 23 differentially expressed metabolites were found. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that these metabolites were related to glutathione metabolism, amino acid metabolism, glucose metabolism, the N -methyl-D -aspartic acid (NMDA) receptor pathway, and the γ -aminobutyric acid (GABA) receptor pathway. Conclusion . Glutathione metabolism, amino acid metabolism, glucose metabolism, NMDA receptors, and GABA receptors may be related to the pathogenesis of presbycusis and may be the material basis underlying the correlation between presbycusis and kidney deficiency in TCM.